Fuzzy logic - Baldwin, J. F (Wiley, 1996)
The rapid growth of data and information confronting many in industry and business has created a need for extracting knowledge out of such data. Fuzzy logic is one of the techniques used within this area of computational and statistical tools. It has been a major commercial success, with many real-world applications including industrial control, medical and financial applications, and incorporation into consumer goods. Fuzzy sets generalise data and enable knowledge to be expressed as linguistic rules, giving a powerful and robust framework. This book discusses many existing applications and outlines the direction of future developments in fuzzy logic.